Dimeric FeFe-hydrogenase mimics bearing carboxylic acids: Synthesis and electrochemical investigation. (8th January 2016) - Garrett, Benjamin R.; Awad, Amneh; He, Mingfu; Click, Kevin A.; Durr, Christopher B.; Gallucci, Judith C.; Hadad, Christopher M.; Wu, Yiying
Graphical abstract: The electrochemical study presented provides valuable insight into degradation pathways of FeFe hydrogenase mimics. The first electrochemical study of dimeric FeFe complexes indicate that the intermolecular bridged complexes degrade upon reduction to form the bidentate species [Fe2 (CO)4 ( κ 2 -Ph2 PCH2 N(Ar)CH2 PPh2 )]. A route for the electrochemical degradation pathway is presented. Abstract: Hydrogen is expected to be important for future sustainable energy applications. Recent interest in adsorbing water splitting catalysts on a semiconductor surface for electrocatalytic hydrogen production warrants careful study of electrocatalysts with functional groups capable of binding to a surface. The monomeric complex Fe2 ( μ -S2 (CH2 )3 )(CO)5 PPh2 C6 H4 CO2 H (S2 (CH2 )3 = 1, 3-propanedithiolate, pdt) and the dimeric complexes [Fe2 ( μ -pdt)(CO)5 2 ( μ, κ 1, κ 1 -Ph2 PCH2 N(Ar)CH2 PPh2 )] (Ar = p -CO2 H-Ph, 3, 5-CO2 HPh, p -CH2 CO2 HPh, m -CO2 H-Ph) bearing carboxylic acid functional groups have been prepared. The first electrochemical study of these dimeric FeFe complexes indicate that the complexes degrade upon reduction to form the species [Fe2 ( μ -pdt)(CO)4 ( κ 2 -Ph2 PCH2 N(Ar)CH2 PPh2 )]. A route is proposed for the formation of [Fe2 ( μ -pdt)(CO)4 ( κ 2 -Ph2 PCH2 N(Ar)CH2 PPh2 )] from [Fe2 ( μ -pdt)(CO)5 2 ( μ, κ 1, κ 1 -Ph2 PCH2 N(Ar)CH2 PPh2 )] and a crystal structure of an intermediate in the proposed electrochemical degradation pathway is presented. The electrochemical study presented herein provides valuable insight into degradation pathways of FeFe hydrogenase mimics bearing carboxylic acids amenable to surface immobilization.